Diaphragmatic Herniation through Prosthetic Material after Extrapleural Pneumonectomy: Be Aware of Tumor Recurrence - Pop, Daniel; Cohen, Charlotte; Schneck, Anne-Sophie; Nadeemy, Ahmad S.; Venissac, Nicolas; Mouroux, Jerome (The Thoracic and Cardiovascular Surgeon Reports, 2013)
Extrapleural pneumonectomy (EPP) is indicated in selected group of patients with pleural mesothelioma. Diaphragmatic reconstruction represents a part of this complex operation. We present the case of a late diaphragmatic gastric herniation through prosthetic material after EPP.
Keywords: pleural mesothelioma; extrapleural pneumonectomy; complications